Insoluble Solids in Brazilian and Floridian Acai (Euterpe oleraceae Mart.) - E. Smith, Robert; Eaker, Janete; Tran, Kevin; Goerger, Michael; Wycoff, Wei; U. O. Sabaa-Srur, Armando; M. da Silva Menezes, Ellen (Natural Products Journal, The, 2012)
Brazilian and Floridian acai were found to contain 24% insoluble solids. They were dark brown and were not soluble in hexane, methanol or water. When 6 N HCl was added to the insoluble solids, they turned red, as do anthocyanins. The solids were analyzed by CP-MAS 13C-NMR. Phenolic C-O, aromatic, glycosidic and aliphatic carbons were detected. About 27% of the solids were hydrolyzed and solubilized by refluxing in conc HCl. Acai is a unique fruit in that it is sold as a product that has a relatively high amount of insoluble solids. So, two things that genuine, unfiltered acai should have are about 24% insoluble solids and the appropriate CP-MAS 13C-NMR spectrum.
Keywords: fruit